Development and validation of a robust and rapid isothermal loop-mediated amplification (LAMP) assay for the detection of Black Sigatoka Disease (Pseudocercospora fijiensis) in bananas : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science (Agricultural Science) at Massey University, Manawatū, New Zealand - Bob, Luania Koi (Massey University, 2020)
Black Sigatoka disease is a serious threat to banana and plantain production. However, the causal agent of the disease, Pseudocercospora fijiensis, is difficult to distinguish from related species associated with yellow Sigatoka disease (P. musicola) and eumusae leaf spot disease (P. eumusae) on the basis of symptomology or morphology. These similarities complicate pathogen identification. Molecular methods such as conventional PCR have been used in diagnosing this disease, but the time and cost of testing as well as the requirement for specialised equipment and infrastructure have limited its usefulness. New molecular approaches are reducing the barriers to molecular testing by allowing testing to be conducted in non-laboratory settings. Given the serious threat of black Sigatoka disease, a simple and rapid isothermal loop-mediated amplification (LAMP) assay has been developed to improve pathogen detection. A potential target region within the mitochondrial small ribosomal subunit (ssRNA) gene was identified and a set of four LAMP primers were developed. Initial trials established optimal reaction conditions for the P. fijiensis LAMP assay. These were a 1:8 primer ratio with an amplification temperature of 60˚C and an amplification time of 60 minutes. Laboratory validation of the assay suggests specific amplification in the presence of the target organism with no cross-reaction with several related species and other fungal pathogens of bananas and it detects anything above 9.1 × 10⁶ copies of the target. The LAMP assay was used against foliar and mycelial samples from Papua New Guinea and foliar samples from Fiji. Testing of foliar samples identified P. fijiensis in >90 % of the samples. These results were confirmed using PCR and sequencing. Nuclear ribosomal ITS sequencing suggested that non-target pathogens dominated the mycelium samples. However, LAMP testing indicated P. fijiensis was present in 50% of these samples. These results were confirmed using a PCR marker specific to P. fijiensis. In combination it suggests P. fijiensis was present on culture plates but competing species grew more rapidly. The testing performed suggests the LAMP assay provides a specific test for P. fijiensis that is sensitive enough to identify this pathogen from symptomatic tissue. Further work is needed to develop protocols for field testing and to examine the potential for testing non-symptomatic material.
The following Figures were removed for copyright reasons: Fig 2.1 (=Bakry et al., 2009, Fig 1.1), 2.5 (=Churchill, 2011 Fig 1A), & 2.7 (=Bruce et al., 2015 Fig 7).
Keywords: 300804 Horticultural crop protection (incl. pests, diseases and weeds)